Boundedness for Multilinear Commutators of Marcinkiewicz Integral on Morrey-Herz Spaces with Non Doubling Measures (Analysis in Theory and Applications, 2013)
In this paper, the authors establish the boundedness of multilinear commutators generated by a Marcinkiewicz integral operator and a RBMO$(μ)$ function on homogeneous Morrey-Herz spaces with non doubling measures.
Keywords: Marcinkiewicz integral; commutator; Morrey-Herz space; non doubling measure; RBMO function.